PyIT2FLS: A New Python Toolkit for Interval Type 2 Fuzzy Logic Systems - Haghrah, Amir Arslan; Ghaemi, Sehraneh (2019)
SoftwareX, Volume 30, May 2025, 102146 Fuzzy logic is an accepted and well-developed approach for constructing verbal models. Fuzzy based methods are getting more popular, while the engineers deal with more daily life tasks. This paper presents a new Python toolkit for Interval Type 2 Fuzzy Logic Systems (IT2FLS). Developing software tools is an important issue for facilitating the practical use of theoretical results. There are limited tools for implementing IT2FLSs in Python. The developed PyIT2FLS is providing a set of tools for fast and easy modeling of fuzzy systems. This paper includes a brief description of how developed toolkit can be used. Also, three examples are given showing the usage of the developed toolkit for simulating IT2FLSs. First, a simple rule-based system is developed and it's codes are presented in the paper. The second example is the prediction of the Mackey-Glass chaotic time series using IT2FLS. In this example, the Particle Swarm Optimization (PSO) algorithm is used for determining system parameters while minimizing the mean square error. In the last example, an IT2FPID is designed and used for controlling a linear time-delay system. The code for the examples are available on toolkit's GitHub page: https://github.com/Haghrah/PyIT2FLS. The simulations and their results confirm the ability of the developed toolkit to be used in a wide range of the applications.